Podstawy stosowania kar wolnościowych w kodeksie karnym z 1997 r. po nowelizacji z 20 lutego 2015 r. - Kokot, Rajnhardt (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is devoted to selected issues of the statutory principles of applying non- custodial penalties introduced into the Polish criminal law system by the amendment of 20th of February 2015. In the preliminary part of the article the basic assumptions of the directions of the reform are presented, together with the aims and the tasks that it is to accomplish.The expression of the essential revaluation in penal policy are regulations of Art. 37a c.c., Art. 37b c.c. and Art. 75a § 1 c.c. discussed in the paper, which in the science of law are believed to be the pillars of that reform and are, according to the legislator’s intentions, to realize the rule of the primacy of non-custodial penalties better than the previous normalizations. The author’s attention is drawn to the most arguable issues in the field of these regulations. Among those issues the most crucial seems to be the matter of their legal nature, the controversies and the doubts arising from the interpretation of the elements of their statutory structure, the premises of implementation and predictable results they can cause in the realm of the justice. The final part of the article comprises comments and reflections devoted to the evaluation of the introduced changes, their validity and purposefulness and to the perspectives of their functioning within the legal system.
Keywords: nowelizacja kodeksu karnego; prawo karne; kara; kara pozbawienia wolności; ograniczenie wolności; grzywna; kary niepolegające na pozbawieniu wolności; wyrok; polityka karna; reforma; sankcja; dyrektywy